2009
DOI: 10.1152/ajpheart.01246.2008
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 modulates VEGF-A-mediated Akt signaling and capillary survival in the developing retina

Abstract: modulates VEGF-A-mediated Akt signaling and capillary survival in the developing retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 39 publications
8
45
0
Order By: Relevance
“…This observation is consistent with increased activation of survival and proliferative pathways in endothelial cells that are isolated from TSP-1-null mice (Wang et al 2006). In addition, elevated levels of Akt phosphorylation are seen in the retinas of TSP-1-null mice (Sun et al 2009). Because Akt mediates survival of endothelial cells, the data indicate that TSP-1 inhibits angiogenesis by antagonizing survival pathways while also activating apoptotic pathways.…”
Section: Vegf Bioavailability and Activitysupporting
confidence: 76%
“…This observation is consistent with increased activation of survival and proliferative pathways in endothelial cells that are isolated from TSP-1-null mice (Wang et al 2006). In addition, elevated levels of Akt phosphorylation are seen in the retinas of TSP-1-null mice (Sun et al 2009). Because Akt mediates survival of endothelial cells, the data indicate that TSP-1 inhibits angiogenesis by antagonizing survival pathways while also activating apoptotic pathways.…”
Section: Vegf Bioavailability and Activitysupporting
confidence: 76%
“…Ligation of CD47 by physiological concentrations of TSP1 inhibits VEGF-induced cGMP synthesis in endothelial cells (19,20) eNOS, soluble guanylate cyclase, and cGMP-dependent protein kinase are known targets of this CD47 signal (49,50). Direct inhibition of VEGFR2 activation adds a much broader control of this angiogenic pathway via CD47 and is consistent with the elevated Akt phosphorylation reported in retinas of TSP1-null mice (23). Akt phosphorylation is inhibited by engagement of CD47, which, in addition to controlling activation of eNOS, controls a broad range of prosurvival signaling in endothelial cells (2,51).…”
Section: Discussionsupporting
confidence: 61%
“…Although TSP1 has been recognized as an endogenous angiogenesis inhibitor for 20 years, the receptors and molecular mechanisms that mediate this activity remain controversial (11,23,43). Our data reveal a new mechanism by which TSP1 FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans have suggested the importance of CD36 function in both lipid uptake and inflammatory processes (9). Increased CD36 expression on monocytes has been linked to monocyte activation in the diabetic state (10,11), and the levels of a circulating CD36 form in plasma have been related to insulin resistance and atherosclerotic plaque instability (12,13). Common CD36 genetic polymorphisms have been associated with risk of the metabolic syndrome (14), diabetes-linked coronary disease (15), and stroke (16) with variants that reduced CD36 protein expression associating with a protective atherogenic lipid profile (17).…”
mentioning
confidence: 99%